THE HISTORY AND DEVELOPMENT OF GAMAT MUSIC AS A PROTOTYPE OF BANDAR ART IN THE WEST SUMATERA COASTAL AREA (PESISIR) - Martarosa Martarosa (Humaniora, 2016)
At the end of the 19th century and the beginning of 20th century, the city of Padang has been dubbed the metropolis of the island of Sumatera. This is because the population of the Europeans who live there is relatively higher than other cities in Sumatera. An influence of this condition appears to be the phenomenon of Western-style music which was introduced to the indigenous peoples (Bandar natives). The appropriation of this musical style from various cultures such as of Portuguese (European), Malay and Minangkabau eventually became known as Gamat. Nowadays, the well-known Gamat is part of the identity of the culture, especially for Minangkabau in the West Sumatera coastal area.